Effect of sociodemographic, clinical-prophylactic and therapeutic procedures on survival of AIDS patients assisted in a Brazilian outpatient clinic Efeitos de fatores sociodemográficos, clínico-profiláticos e terapêuticos na sobrevida de pacientes com aids acompanhados em uma unidade ambulatorial brasileira - Dario José Hart Pontes Signorini; Claudia Torres Codeço; Marilia Sá Carvalho; Dayse Pereira Campos; Michelle Carreira Miranda Monteiro; Marion de Fátima Castro de Andrade; Jorge Francisco da Cunha Pinto; Carlos Alberto Morais de Sá (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2005)
The Brazilian AIDS Program offers free and universal access to antiretroviral therapy. This study investigates the influence of sociodemographic, clinical-prophylactic and therapeutic factors on survival, after AIDS diagnosis, in an open cohort of 1,420 patients assisted in a university hospital in the city of Rio de Janeiro (1995 _ 2002). Kaplan-Meier and Cox proportional hazards models were used to estimate the effect of variables in the three dimensions studied. The overall survival time of the upper quartile was 24 months (CI95%= 20.5-27.5), increasing from 14 months, in 1995, to 46 months, in 1998. We found a protective effect of heterosexual behavior against death that could be attributed to the increasing female-to-male sex ratio in the cohort, which coincided with the time of therapy introduction. Low schooling, hospital admission and lack of follow-up were identified as risk factors for death; PCP and Toxoplasmosis prophylaxis were protective. The number of attempts required to consolidate the antiretroviral therapy showed no significant effect on survival. The full model, which includes the number of antiretroviral drugs in the regimen, confirmed the triple therapy as the best regimen. This study brings important information for designing guidelines to deal with different aspects related to the practical management of patients and their behavior, thus contributing to the success of the program of free access to antiretroviral therapy implemented in Brazil. O programa Brasileiro de DST/AIDS oferece acesso livre e universal à terapia anti-retroviral. Este estudo investiga a influência dos fatores sociodemográficos, clínico-profiláticos e terapêuticos na sobrevida, após o diagnóstico de AIDS, em uma coorte aberta de 1.420 pacientes atendida em hospital universitário na Cidade do Rio de Janeiro (1995-2002). Kaplan-Meier e modelo de risco proporcional de Cox foram usados para estimar os efeitos das variáveis nas três dimensões estudadas. O tempo de sobrevida global no quartil superior foi de 24 meses (IC95%= 20,5-27,5), aumentando de 14 meses, em 1995, para 46 meses, em 1998. Encontrou-se um efeito protetor do comportamento heterossexual contra o risco de morte que pode ser atribuído à proporção crescente de mulheres na coorte, que coincide com a introdução da terapia. Baixa escolaridade, admissão hospitalar e ausência de seguimento nas consultas foram fatores de risco, enquanto a profilaxia para PCP e para toxoplasmose foram protetoras. O número de tentativas requeridas para consolidar a terapia anti-retroviral mostrou não ter efeito significativo na sobrevida. O modelo completo, incluído o número de drogas anti-retrovirais do esquema, confirmou a tripla terapia como o melhor esquema. Este estudo traz importantes informações para definir orientações que lidem com diferentes aspectos relacionados com o manuseio prático de pacientes e seus comportamentos, desta forma contribuindo para o sucesso do livre acesso à terapia anti-retroviral no controle da AIDS.